2024
DOI: 10.1017/s0021932024000117
|View full text |Cite
|
Sign up to set email alerts
|

Does epidemiological evidence support the success story of Uganda’s response to COVID-19?

Nicolas Laing,
Sophie Mylan,
Melissa Parker

Abstract: Uganda has received praise for its success in dealing with the COVID-19 pandemic. This opinion piece uses publically available data from Johns Hopkins University to suggest that it is far from clear whether the Public Health and Social Measures (PHSM) introduced in Uganda influenced the course of the first outbreak. In addition, the analysis of data from the second and third waves in Uganda suggest that government action had little or no effect on these outbreaks. The dominant narrative of successful PHSM, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…To the extent that it is possible to use the published Ugandan COVID-19 tracking data, declines in reported infections mostly do not correspond with the introduction of control measures. For example, using available epidemiological COVID-19 data for Uganda and South Africa collated by John Hopkins University, Laing et al (2024) have suggested that control measures might have had some influence on the first outbreak but had little or no effect on the second and third wave. Instead, analysis of the data suggests rapid uncontrolled spread and spontaneous resolution of outbreaks.…”
Section: Ugandamentioning
confidence: 99%
“…To the extent that it is possible to use the published Ugandan COVID-19 tracking data, declines in reported infections mostly do not correspond with the introduction of control measures. For example, using available epidemiological COVID-19 data for Uganda and South Africa collated by John Hopkins University, Laing et al (2024) have suggested that control measures might have had some influence on the first outbreak but had little or no effect on the second and third wave. Instead, analysis of the data suggests rapid uncontrolled spread and spontaneous resolution of outbreaks.…”
Section: Ugandamentioning
confidence: 99%